Necessity for craniospinal irradiation of germinoma with positive cytology without spinal lesion on MR imaging—A controversy. Issue 1 (25th June 2021) - Kanamori, Masayuki; Takami, Hirokazu; Suzuki, Tomonari; Tominaga, Teiji; Kurihara, Jun; Tanaka, Shota; Hatazaki, Seiji; Nagane, Motoo; Matsuda, Masahide; Yoshino, Atsuo; Natsumeda, Manabu; Yamaoka, Masayoshi; et al.
Abstract: Background: Cerebrospinal fluid (CSF) cytology and spinal MR imaging are routinely performed for staging before treatment of intracranial germinoma. However, the interpretation of the results of CSF cytology poses 2 unresolved clinical questions: (1) Does positive CSF cytology correlate with the presence of spinal lesion before treatment? and (2) Is craniospinal irradiation (CSI) necessary for patients with positive CSF cytology in the absence of spinal lesion? Methods: Multicenter retrospective analyses were performed based on a questionnaire on clinical features, spinal MR imaging finding, results of CSF cytology, treatments, and outcomes which was sent to 86 neurosurgical and 35 pediatrics departments in Japan. Pretreatment frequencies of spinal lesion on MR imaging were compared between the patients with positive and negative cytology. Progression-free survival (PFS) rates were compared between patients with positive CSF cytology without spinal lesion on MR imaging treated with CSI and with whole brain or whole ventricular irradiation (non-CSI). Results: A total of 92 germinoma patients from 45 institutes were evaluated by both CSF cytology and spinal MR images, but 26 patients were excluded because of tumor markers, the timing of CSF sampling or incomplete estimation of spinal lesion. Of the remaining 66 germinoma patients, spinal lesions were equally identified in patients with negative CSF cytology and positive cytology (4.9% and 8.0%, respectively). Eleven patients treated with non-CSI had excellent PFS comparable to 11 patients treated with CSI. Conclusion: CSI is unnecessary for germinoma patients with positive CSF cytology without spinal lesions on MR imaging.